Analysis of Collection Management Practices in Esa Unggul University Library - Nisa, Andi Khaerun (Literatify : Trends in Library Developments, 2020)
The practices of collection management at the Esa Unggul University Library is still being distorted. There are several cases of collections that should have been weeded but still maintained which are the limitations of human resources to make the process to be inhibited and inefficient, budgeting, and space in the library so that the procurement of new bookshelves is still delusion. The data were obtained through observation, interview with librarians and from the official website of Esa Unggul University Library. The practices of collection management at Esa Unggul University Library, including: deselection, preservation and conservation, and storage. The deselection practice is scheduled every year. The preservation and conservation practices are carried out by termite and bookbinding methods on books, while for the electronic collections by duplicating files. Storage practices, Mezanin’s shelf as a special space for old and copied books. ABSTRAK Pengelolaan koleksi di Perpustakaan Universitas Esa Unggul dalam praktiknya masih terjadi distorsi. Ada beberapa kasus koleksi yang seharusnya sudah disiangi namun tetap dipertahankan, keterbatasan SDM membuat prosesnya menjadi terhambat dan tidak efisien, dan karena keterbatasan anggaran dan ruang di perpustakaan sehingga pengadaan rak buku baru masih sebatas angan-angan. Data dikumpulkan melalui observasi, wawancara kepada pustakawan dan dari hasil studi dokumen pada website resmi Perpustakaan Universitas Esa Unggul. Praktik pengelolaan koleksi di Perpustakaan Universitas Esa Unggul, meliputi: praktik deseleksi, preservasi dan konservasi, dan storage. Praktik deseleksi dilakukan secara terjadwal yakni setiap tahun. Praktek preservasi dan konservasi dilakukan dengan metode umpan rayap dan penjilidan pada buku, sedangkan untuk koleksi elektronik dilakukan penggandaan file. Praktek storage, Rak Mezanin sebagai tempat penyimpanan khusus koleksi buku lama dan buku fotocopy.